Employer-employee relations and employee engagement in a tertiary institution in Benin-City, Edo State - Arimie, Chukwuyem Joel (goodwood publishing, 2019)
Purpose: This study aimed to explore the relationship between employer-employee relations and employee engagement in a tertiary institution in Edo State. Research methodology: Semi-structured interviews were conducted on a cross-section of management staff, heads of department, and units in the University. A descriptive method was adopted for data analysis. Results: The results of this study revealed that employee engagement is a by-product of employer-employee relations and the quality of the relationship is one of the most critical factors that drive engagement and satisfaction of employees. Limitations: The challenge was the inadequate number of respondents interviewed due to time constraint. Contribution: The study provided insight into the so called